1987
DOI: 10.1063/1.97673
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of reactively sputtered ruthenium dioxide for very large scale integrated metallization

Abstract: We have investigated reactively sputtered films of RuO2 for possible application in very large scale integrated circuits. Sputtering yields stoichiometric ruthenium dioxide in a large window of oxygen pressures and the films are reasonably low stressed in the 10−9 dyn cm−2 range. The resistivity of as deposited films is 40 μΩ cm. The films are excellent barriers against interdiffusion of Si and Al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(47 citation statements)
references
References 11 publications
1
45
0
1
Order By: Relevance
“…These properties recommend RuO 2 as a non-corrosive diffusion barrier for contact metallizations in very large-scale integrated circuits (VLSI), [1,2] for film resistors, for buffer layers of high-T c superconducting films on silicon, [3] and for electrodes of ferroelectric thin films. [4] Furthermore, RuO 2 is frequently used as an electrocatalyst in chlorine production, [5] and has been proposed as a catalyst for the photodecomposition of water.…”
Section: Introductionmentioning
confidence: 99%
“…These properties recommend RuO 2 as a non-corrosive diffusion barrier for contact metallizations in very large-scale integrated circuits (VLSI), [1,2] for film resistors, for buffer layers of high-T c superconducting films on silicon, [3] and for electrodes of ferroelectric thin films. [4] Furthermore, RuO 2 is frequently used as an electrocatalyst in chlorine production, [5] and has been proposed as a catalyst for the photodecomposition of water.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Ruthenium oxide (RuO) is a conductive oxide with excellent diffusion barrier quality, good chemical and thermal stability, and a high work function (∼5 eV), which makes it a good deep charge trapping medium in the dielectric film. [10][11][12][13] Previously, Maikap et al 14 reported that nc-RuO could be included in the HfO 2 /Al 2 O 3 high-k film using the atomic layer deposition (ALD) method. Authors have also demonstrated that excellent memory functions were obtained with the nc-RuO embedded ZrHfO film prepared by the sputter deposition method followed by a post deposition annealing (PDA) step.…”
mentioning
confidence: 99%
“…Films of RuO 2 have also been considered for metallizations in integrated circuits. [30][31][32][33][34][35] The values of the heats of formation of the transition metal oxides are comparable to those of the transition metal nitrides and indicate good thermal stability. 36 The surface morphology of RuO 2 films is reported to remain smooth after rapid thermal annealing up to 900ЊC for 10 s in argon, nitrogen, and oxygen.…”
Section: Discussionmentioning
confidence: 99%